'I've never felt like that inhibits anything': the gendered frameworks of Hispanic women college students in a STEM program. Issue 5 (3rd July 2020) - Frederick, Angela; Daniels, Heather A.; Grineski, Sara E.; Collins, Timothy W.
ABSTRACT: Under-represented women of color in the STEM pipeline face myriad structural and cultural challenges in these male-dominated fields. Given this context, it is important to examine how these young women employ gendered discourses as they navigate their STEM majors. We report findings from interviews with 16 Hispanic women college students participating in a competitive STEM program at a Hispanic-serving university. These college students employed combinations of feminist and post-feminist narratives to identify and challenge instances of blatant gender diminishment. Most, however, downplayed gender disparities in their fields, and few anticipated the gender inequalities they are likely to face as the result of these structural disparities.